Prognostic value of the controlling nutritional status score in patients with myelodysplastic syndromes - Chen, Qiuni; Chen, Kankan; Wang, Sumei; Zhang, Lijuan; Shi, Yuye; Tao, Shandong; He, Zhengmei; Wang, Chunling; Yu, Liang (Frontiers in Nutrition, 2022)
BACKGROUND: Myelodysplastic syndromes (MDS) are a heterogeneous spectrum of clonal hematopoietic disorders with varying degrees of cytopenia and morphologic dysplasia. The controlling nutritional status (CONUT) score, an easy-to-use tool for assessing the nutritional status, was reported as an independent prognostic factor in cancer patients. However, its role in patients with MDS is unclear. OBJECTIVE: We aimed to explore the impact of CONUT score on the prognosis of patients with MDS, which is of great significance for clinical treatment. METHODS: A total of 121 patients with MDS were analyzed. The CONUT score was calculated prior to therapy. The bio-informatics tool X-tile was used to define the CONUT score and the threshold of 4 points was determined to predict the prognosis. Patients were divided into CONUTlow and CONUThigh groups, and the characteristics were compared between two groups. RESULTS: Results show that CONUTlow was associated with better OS (overall survival) than CONUThigh patients (Median OS, 30.20 months versus 19.63 months, P=0.0003). However, there were no statistical differences in PFS (progression-free survival) between the two groups (P=0.2683). Results of univariate and multivariate COX proportional hazard analysis adjusted for bone marrow blasts level, platelet count, Prognostic Scoring System (IPSS) scores, gender, and hemoglobin (Hb) level showed CONUT score was useful in the evaluation standard of OS of MDS (hazard ratio (HR) 2.297, 95%CI 1.441-3.663, P＜0.001). CONCLUSIONS: The CONUT, as a novel immuno-nutritional biomarker, may be useful in predicting the OS of MDS.